2014
DOI: 10.1177/1049732314550004
|View full text |Cite
|
Sign up to set email alerts
|

“I Am a Waste of Breath, of Space, of Time”

Abstract: According to recent research on eating disorders, heavy users of pro-anorexia (pro-ana) sites show higher levels of disordered eating and more severe impairment of quality of life than non-heavy users. A better understanding of how pro-ana members self-present in the virtual world could shed some light on these offline behaviors. Through discourse analysis, I examined the metaphors the members of a pro-ana group invoked in their personal profiles on a popular social networking site, to talk about the self. I a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…39 However, using these groups for social support may be problematic, as studies suggest that these groups may lead to development of a shared social identity that inhibits authentic and meaningful recovery from an eating disorder. 40,41 …”
Section: Discussionmentioning
confidence: 99%
“…39 However, using these groups for social support may be problematic, as studies suggest that these groups may lead to development of a shared social identity that inhibits authentic and meaningful recovery from an eating disorder. 40,41 …”
Section: Discussionmentioning
confidence: 99%
“…Here participants drew on typical ED and Pro-Ana discourses which suggested complete preoccupation with weight, shape and a commitment to perfecting the self via dietary restraint (Fox et al 2005;Gavin, Rodham & Poyer, 2008;Bates, 2015). The accounts made relevant the speculative nature within which the Pro-Ana community attempted to identify F o r P e e r R e v i e w 'legitimate' sufferers and 'wannabees' (Bates, 2015). One narrator portrayed a growing discomfort with constructions of EDs online, positioning 'withdrawal' as resulting from a need to prove that EDs could exist outside of this environment.…”
Section: Study Limitations and Future Research Endeavorsmentioning
confidence: 99%
“…For example, Mantella (2007) found that over half of pro-ana bloggers reported that they were motivated to blog in order to receive social and emotional support. Members of online pro-anorexic communities often feel a sense of camaraderie with others who suffer from similar issues (Csipke & Horne, 2007;Dias, 2013;Falk, 2001). These types of communities provide anorexics with a sense of temporary relief from the hostility they experience in their day-to-day lives (Brotsky & Giles, 2007).…”
Section: Social Identity and Body Imagementioning
confidence: 99%